Senecio sangayensis (Asteraceae, Senecioneae): a striking new species from the Ecuadorian highlands - Vásquez, Diana L. A.; Calvo, Joel (Phytotaxa, 2016)
Senecio sangayensis, a putative endemic species from the eastern Ecuadorian Cordillera, is described as a new species. It is chiefly distinguished by its habit, striking racemiform synflorescence composed of dense cymose-corymbs subtended by triangular-ovate bracts, and life-history strategy. This new species is known from the páramo of the Sangay National Park. Its IUCN conservation status is preliminarily assessed as Endangered (EN).